Xylans inhibit enzymatic hydrolysis of lignocellulosic materials by cellulases - Zhang, Junhua; Tang, Ming; Viikari, Liisa (Bioresource technology, 2012)
[Display omitted] ► Xylan clearly inhibited the enzymatic hydrolysis of cellulose by cellulase. ► Xylan clearly inhibited the cellulose hydrolysis by individual EGII, CBHI and CBHII. ► The solubility of oat spelt xylan did not clearly affect the hydrolysis of cellulose. ► After the addition of xylans, cleaved cellobiose units by CBHI from cellulose chain decreased. Hemicelluloses have been found to be physical barriers in the hydrolysis of cellulose, and prevent the access of enzymes to cellulose surface. In addition, soluble hemicelluloses may strongly inhibit the cellulase activity. In this work, birchwood xylan clearly inhibited the enzymatic hydrolysis of wheat straw, Avicel and nanocellulose by cellulases. Hydrolysis efficiencies of cellobiohydrolase I (CBHI, from Thermoascus aurantiacus), cellobiohydrolase II (CBHII, from Trichoderma reesei) and endoglucanase II (from T. aurantiacus) were clearly inhibited by birchwood xylan, respectively. The strongest inhibitory effect of birchwood xylan was observed on the hydrolysis of Avicel by CBHI and CBHII, as a dramatically decreased formation of the main product, cellobiose. After additions of soluble and insoluble oat spelt xylan, cleaved cellobiose units by CBHI from cellulose chain decreased from 8 to 4 and 6, respectively. The results in this work demonstrated that xylans clearly inhibited the hydrolysis efficiencies of both endoglucanase and cellobiohydrolase.